Photoproduction of π0-Mesons from the Nucleon and Deuteron - Darwish, Eed Mohamed; Hemmdan, Amel; El-Shamy, Nesreen T. (Makara Journal of Science, 2016)
The photoproduction of π0-mesons from the nucleon and deuteron has been studied for incidents of photon energies up to 1.5 GeV. By using the MAID-2007 model for the process on the nucleon, we predict results for the unpolarized and helicity-dependent total cross sections of the semi-exclusive reaction γd→π0X (X=np+d) with the inclusion of rescattering effects. We find that rescattering effects yield a substantially large contribution. The extracted results are compared with the available experimental data and a satisfactory agreement is obtained. In addition, the contribution of γd→π0X (X=np+d) to the finite GDH integral has been evaluated by explicit integration up to 1.5 GeV and a total value of 256.96 µb has been obtained. Convergence of the GDH integral has been reached.